UJI AKTIVITAS ANTIINFLAMASI DARI EKSTRAK METANOL DAUN NANGKA (Artocarpus heterophyllus Lam.) TERHADAP TIKUS YANG DIINDUKSI KARAGENAN LAMBDA - Ira Asmaliani (Fakultas Farmasi UMI, 2016)
Inflammation is body response to prevent infection or tissue damage caused toxin or microbe in the body. Inflammation is usually treated with drugs known as NSAIDs (non-steroidal anti-inflammation drugs). However, the treatment with NSAID drugs often has side effects such as stomach irritation. Lately, the researchers are very aggressively finding an alternative therapy in treating inflammation by using medical herbal. The purpose of this study was to determine an anti-inflammatory activity of jackfruit leaves (Artocarpus heterophyllus Lam.) in male rats. Animal models were made by induced lambda carrageenan by intraplantar. This study consist of 4 groups: negative control (Na-CMC), methylprednisolone dose 45 mg / kg, methanol extract of jackfruit leaves (EMDN) doses 75 mg / kg and 150 mg / kg. Parameters were tested by measuring the volume of feet for 8 hours after induction of carrageenan using the plethysmometer. The results showed that the methanol extract of jackfruit leaves (EMDN) dose of 150 mg/kgbw has anti-inflammatory effects by inhibiting oedema in rats with 55.4% better than methanol extract of jackfruit leaves (EMDN) dose of 75 mg/kgbw with 23.9%.